Effect of chemical composition of calcined bauxite aggregates on mechanical and physical properties for high friction surface course. (4th October 2021) - Li, Song; Xiong, Rui; Dong, Xiaoming; Sheng, Yanping; Guan, Bowen; Zong, Youjie; Xie, Chao; Zhai, Jiahui; Li, Chuang
Highlights: The indicator SiO2 /Al2 O3 has significant impact on road performance of calcined bauxite. The PSVf is significantly correlated with mineral characteristics of calcined bauxite. The incorporation of calcined bauxite can well improve skid resistance of asphalt mixture. Abstract: This paper attempts to show the impact of chemical components on the mechanical and physical performance of calcined bauxite, especially the long-term skid resistance. Firstly, the mechanical and physical properties of five types of calcined bauxites including, the polished stone value (PSV), crush value, Los Angeles Abrasion value (LAA), adhesion property, bulk density and water absorption were tested. The X-ray fluorescence (XRF) and X-ray diffraction (XRD) were applied to examine the chemical and mineral components of aggregate. The Pearson correlation coefficient and Pearson correlation coefficient matrix by Statistic Package for Social Science (SPSS) were utilized to study the relationship between chemical components and mechanical, physical properties of calcined bauxite. Then, the long-term skid resistance of calcined bauxite aggregate was carried out in the laboratory by accelerated polish machine and British Pendulum Tester. The polishing mechanism and the influence of chemical components on the skid resistance of calcined bauxite aggregates were gained by linear regression methods. The asymptotic model was adopted to fit the relationship between British pendulum number (BPN) and polish times. The results indicate that the chemical compositions of calcined bauxite aggregate including Al2 O3 and SiO2 along with indicator SiO2 /Al2 O3 show significant impact on the mechanical and physical properties of calcined bauxites. The final value of PSV (PSVf ) is significantly correlated with average grain size (D), corundum, mullite and Aggregate Hardness Parameter (AHP) of calcined bauxite. The asymptotic model can describe the decay process of polish of calcined bauxite with polish time. The PSVn can be expressed with PSVf and SiO2 /Al2 O3 by linear equation. In addition, the incorporation of calcined bauxite improves MPD (Mean Profile Depth) and BPN of limestone asphalt mixture. This provides a new and interesting way for selecting suitable aggregate used in the pavement surface layer.